Evidence for enhanced Bruton's tyrosine kinase activity in transitional and naïve B cells of patients with granulomatosis with polyangiitis. (17th June 2019) - von Borstel, Anouk; Abdulahad, Wayel H; Sanders, Jan Stephan; Rip, Jasper; Neys, Stefan F H; Hendriks, Rudi W; Stegeman, Coen A; Heeringa, Peter; Rutgers, Abraham; Corneth, Odilia B J
Abstract: Objectives: To determine Bruton's tyrosine kinase (BTK) protein and phosphorylation levels in B cell subsets of granulomatosis with polyangiitis (GPA) patients and to investigate the effect of BTK blockade on in vitro B cell cytokine production, subset distribution and (auto)antibody production. Methods: BTK protein and phosphorylation levels were determined by flow cytometry in peripheral blood B cells of 29 untreated GPA patients [9 active and 20 remission GPA patients (10 ANCA– and 10 ANCA+)], 9 age- and sex-matched healthy controls (HCs) and 9 untreated active RA patients. The effect of BTK blockade on in vitro B cell cytokine production, subset distribution and (auto)antibody production was determined in the same donors in peripheral blood mononuclear cell cultures. Results: BTK protein levels were significantly increased in transitional and naïve B cells of active GPA and RA patients compared with remission GPA patients and HCs. Both B cell subsets of active patients were more sensitive to B cell receptor stimulation, as BTK and phospholipase Cγ2 phosphorylation were increased in these patients. In vitro BTK blockade had profound effects on B cell cytokine production, plasma cell formation and (auto)antibody production in both GPA patients and HCs. Interestingly, the effect of BTK blockade was less pronounced in active GPA patients, possibly due to increased activation of B cells. Conclusion: We show that BTK protein and phosphorylation levels are most profoundly increased in newly emerging B cells of active GPA patients compared with remission patients. BTK blockade greatly inhibits in vitro B cell effector functions in GPA patients and HCs. These promising data identify BTK as an interesting novel therapeutic target in the treatment of GPA.